PENGGUNAAN MEDIA COUNTING BOX UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS I SEKOLAH DASAR - Rumiah Siregar; Parulian Siregar; Resdilla Pratiwi (EDU RESEARCH, 2024)
The purpose of this research is to evaluate the effectiveness of using Counting Box media for teaching addition and subtraction of numbers from 1 to 20 to first-grade students at SD Negeri 100100 Simaninggir in Batang Onang District. It also aims to assess whether the use of Counting Box media enhances mathematics learning outcomes for these students. This study employs a classroom action research (CAR) methodology, structured with a pre-cycle, cycle I, and cycle II design. The research population consists of 14 first-grade students, and data collection methods include observations and tests. The data were analyzed using 1) qualitative descriptions obtained from student observations, 2) quantitative descriptions obtained from student learning outcomes through tests. Based on student learning outcomes in the pre-cycle, an average score of 63.57 was obtained from 14 students, only 4 (28.57%) reached the KKM and 10 students (71.43%) did not reach the KKM. In cycle I obtained an average score of 69 from 14 students, only 8 students (57%) achieved the KKM and 6 students (43%) did not reach the KKM and experienced an increase in cycle II with an average score of 86 from 14 students 13 students (93%) have reached the KKM and only 1 (7%) student has not reached the KKM with an average increase of 17. The results of this study indicate that the use of Counting Box Media is effective and can improve student learning outcomes Class I of SD Negeri 100100 Simaninggir, Batang Onang District.